2014
DOI: 10.1371/journal.pmed.1001660
|View full text |Cite
|
Sign up to set email alerts
|

Association between Melanocytic Nevi and Risk of Breast Diseases: The French E3N Prospective Cohort

Abstract: Using data from the French E3N prospective cohort, Marina Kvaskoff and colleagues examine the association between number of cutaneous nevi and the risk for breast cancer. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
0
11
1
Order By: Relevance
“…A correlated SNP rs738322 (r-sq=0.34, D’=0.71) located in the PLA2G6 gene has previously been associated with cutaneous nevi 20 . Interestingly, two recent independent studies recently reported a link between cutaneous nevi and breast cancer 21 , 22 and it is possible that this link can be partly explained through a shared genetic origin between cutaneous nevi and mammographic density.…”
Section: Resultsmentioning
confidence: 99%
“…A correlated SNP rs738322 (r-sq=0.34, D’=0.71) located in the PLA2G6 gene has previously been associated with cutaneous nevi 20 . Interestingly, two recent independent studies recently reported a link between cutaneous nevi and breast cancer 21 , 22 and it is possible that this link can be partly explained through a shared genetic origin between cutaneous nevi and mammographic density.…”
Section: Resultsmentioning
confidence: 99%
“…46 In epidemiology studies, the association of TYRP1 with nevi and melanoma has been reported, 47, 48 and two studies also proposed that nevi (melanoma) and breast cancer may share genetic factors. 49, 50 Therefore, TYRP1 could be a candidate gene for different diseases through different mechanisms that require further studies to reveal.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies found that women with more nevi were more likely to be diagnosed with breast cancer than their counterparts who reported no nevi, which suggested the number of cutaneous nevi may reflect plasma sex hormone levels [4,5]. In addition, postmenopausal women with six or more nevi had significantly higher levels of free oestradiol and free testosterone than those with no nevi, indicating the potential utility of nevi as a marker of postmenopausal women's endogenous sex hormone levels.…”
Section: Introductionmentioning
confidence: 96%